A atuação de grandes grupos educacionais no ensino superior privado: realidades e repercussões - Lima, Kellwin Augusto Leray de (2018)
The theme about the paths taken by higher education and the subjects that inhabit it, arouses debates around the world involving, among other issues, pedagogical and management projects. The present research aims to: analyze the performance of large educational groups in Private Higher Education and its repercussions and impacts on Brazilian education. The main focus of the study is the historical privatization of this level of education and the current trend of private initiative in the formation of oligopolies, which control dozens of private higher education institutions (IESP), which has repercussions on the organizational reality of the process enrollment and academic training. These groups often use the force of their financial capital to interfere in legal norms of different natures. It should be noted that, as a result of the institutional purchase or merger process, the dynamics of the educational services offered are modified at the level of management and curricular proposals. In this context characterized by the presence of educational companies, one can observe the exponential expansion of vacancies in higher education and the decrease in the quality of the services provided. These developments result in a questionable educational panorama that justifies the urgent need to investigate the impacts of this process, the subjects involved, among other aspects. The methodological approach adopted is defined by the qualitative approach, adopting as procedures the bibliographic review and documentary analysis. The documents analyzed are: memoirs of meetings of a teaching union, annals of national events of educational sector entities, and reports of Parliamentary Inquiry Committees (CPIs) on higher education, as well as statements and balance sheets issued by companies to their shareholders and the financial market. The dissertation is structured in three chapters covering theoretical conceptual systematizations and results of the analyzes in order to meet the proposed objective